Cost-effectiveness analysis of adult pneumococcal conjugate vaccines for pneumococcal disease in Japan - Nakamura, Shigeki; Mikami, Masashi; Hayamizu, Tomoyuki; Yonemoto, Naohiro; Moyon, Camille; Gouldson, Mark; Crossan, Catriona; Vietri, Jeffrey; Kamei, Kazumasa (Expert review of vaccines, 2024)
The 23-valent pneumococcal polysaccharide vaccine (PPSV23) is used in the Japanese National Immunization Program for older adults and adults with increased risk for pneumococcal disease, however, disease incidence and associated burden remain high. We evaluated the cost-effectiveness of pneumococcal conjugate vaccines (PCVs) for adults aged 65 years and high-risk adults aged 60-64 years in Japan. Using a Markov model, we evaluated lifetime costs using societal and healthcare payer perspectives and estimated quality-adjusted life-years (QALYs), and number of prevented cases and deaths caused by invasive pneumococcal disease (IPD) and non-IPD. The base case analysis used a societal perspective. In comparison with PPSV23, the 20-valent PCV (PCV20) prevented 127 IPD cases 10,813 non-IPD cases (inpatients: 2,461, outpatients: 8,352) and 226 deaths, and gained more QALYs (+0.0015 per person) with less cost (-JPY22,513 per person). All sensitivity and scenario analyses including a payer perspective analysis indicated that the incremental cost-effectiveness ratios (ICERs) were below the cost-effectiveness threshold value in Japan (JPY5 million/QALY). PCV20 is both cost saving and more effective than PPSV23 for adults aged 65 years and high-risk adults aged 60-64 years in Japan.